To solve the equation \(- (x - 3)^2 - 3 = 7\), we can start by isolating the quadratic term.
-
Add 3 to both sides of the equation: \[
- (x - 3)^2 = 7 + 3 \] \[
- (x - 3)^2 = 10 \]
-
Multiply both sides by -1: \[ (x - 3)^2 = -10 \]
-
Now, take the square root of both sides: \[ x - 3 = \pm \sqrt{-10} \] Using the fact that \(\sqrt{-10} = i\sqrt{10}\) (where \(i = \sqrt{-1}\)): \[ x - 3 = \pm i\sqrt{10} \]
-
Solve for \(x\): \[ x = 3 \pm i\sqrt{10} \]
Thus, the solutions are: \[ x = 3 + i\sqrt{10} \quad \text{and} \quad x = 3 - i\sqrt{10} \]
Expressing the answer in the standard form \(a + bi\):
- For \(x = 3 + i\sqrt{10}\), we have \(a = 3\) and \(b = \sqrt{10}\).
- For \(x = 3 - i\sqrt{10}\), we have \(a = 3\) and \(b = -\sqrt{10}\).
So the solutions in the standard form \(a \pm bi\) are: \[ x = 3 + i\sqrt{10} \quad \text{and} \quad x = 3 - i\sqrt{10} \]